SPIN: Submitting Sequences Determined at Protein Level to UniProt. Issue 1 (25th May 2018) - Pichler, Klemens; Warner, Kate; Magrane, Michele
Abstract: Public availability of biological sequences is essential for their widespread access and use by the research community. The Universal Protein Resource (UniProt) is a comprehensive resource for protein sequence and functional data. While most protein sequences entering UniProt are imported from other source databases containing nucleotide or 3‐D structure data, protein sequences determined at the protein level can be submitted directly to UniProt. To this end, UniProt provides a Web interface called SPIN. This service enables researchers to make their de novo–sequenced proteins available to the scientific community and acquire UniProt accession numbers for use in publications. This unit explains the process of submitting a protein sequence to UniProt using SPIN. The basic protocol describes all the necessary steps for a single sequence. A support protocol gives guidance on how best to deal with exceptionally large datasets. © 2018 by John Wiley & Sons, Inc.